EKSISTENSI AKAD DALAM TRANSAKSI KEUANGAN SYARIAH - Zubair, Muhammad Kamal; Hamid, Abdul (DIKTUM: Jurnal Syariah dan Hukum, 2016)
This paper will explore the existence of the contract has a crucial role in Islamic financial transactions with a number of implications posed. One of that in Islam there is freedom to determine the contract with all the terms and forms of contract desired by the parties, provided that the contract is voluntary and is not included in the prohibition of sharia’. On this basis, the core of the contract which is carried out in Islam is to create benefits for the parties to the agreement for an Islamic financial transactions.